A Historical Overview of Fire Seasonality in Tallgrass Prairie - Gene Towne (Symphony in the Flint Hills, 2012)
For thousands of years, lightning was the primary source of prairie fires in the Great Plains. Although lightning potentially can strike the ground at any time of the year, more than three-fourths of all lightning strikes in the grasslands occur in July and August.
Keywords: fire; tallgrass; grassland; plains; Great Plains; lightning; prairie; weather; summer; hunters; Stone Age; Anthropogenic; meadow; burning; flames; herbivores; ungrazed; biomass; wildfires; pioneers; Native Americans; bison; cattle; regrowth